Efficacy of Metformin in the Prevention and Management of Paclitaxel Chemotherapy-Induced Peripheral Neuropathy: A Systematic Literature Review - Rizal, Rizal (HM Publisher, 2024)
Background: Peripheral neuropathy is a common side effect of paclitaxel chemotherapy that can cause tingling, numbness, and pain in the hands and feet. Metformin, an antidiabetic drug, shows potential in preventing and managing paclitaxel chemotherapy-induced peripheral neuropathy. This review article aims to evaluate the efficacy of metformin in the prevention and management of peripheral neuropathy due to paclitaxel chemotherapy. Methods: Electronic literature (PubMed, Scopus, Web of Science) was reviewed to find clinical studies examining the efficacy of metformin in the prevention and management of paclitaxel chemotherapy-induced peripheral neuropathy. Results: Eight clinical studies with a total of 542 patients were evaluated. Metformin significantly reduced the risk of developing peripheral neuropathy compared with placebo (OR = 0.54; 95% CI: 0.32-0.91). Metformin significantly reduced neuropathy symptom scores compared with placebo (MD = -1.52; 95% CI: -2.43 to -0.61). Metformin significantly improved patients' quality of life compared with placebo (MD = 0.48; 95% CI: 0.17-0.79). Conclusion: Metformin shows promising efficacy in the prevention and management of paclitaxel chemotherapy-induced peripheral neuropathy.